Impact of glycosylated haemoglobin (HbA1c) levels on outcomes in patients with myocardial infarction - Pandey, Prabhat; Dokania, Neeraj; Pandey, Pooja; Raghuwanshi, Ajay Singh (International Journal of Advances in Medicine, 2021)
Background: People with diabetes have an increased prevalence of atherosclerosis and coronary heart disease (CHD) and experience higher morbidity and mortality after acute coronary syndrome and myocardial infarction than people without diabetes. Diabetes also appears to be a major cause of the higher rate of both short and long-term mortality observed in women hospitalized with acute MI compared to men. Objective of the study was to observe the impact of glycosylated hemoglobin (HbA1c) levels on outcomes in MI. Methods: The prospective observational study was conducted on 200 patients from the age group more than 36 years and lesser than 95 years presented with acute myocardial infarction (STEMI or NSTEMI). Patients were divided into group A (Diabetics) and group B (non-diabetics). Investigations performed were FBS, RBS, HbA1c, CBC, LFT, RFT, lipid profile, ECG and echocardiography. Patients were followed up till discharge/death and all complications like arrhythmias, cardiac failure, cardiogenic shock and re infarction were noted. Results: Majority of the 34.5% patients belongs to the age group of 56-65 years. No significant difference found between the subject population of the diabetic and non-diabetic group. The percentage of mortality in male patients was reported higher in the group having HbAlc level ≥7 (21.15%) in comparison to a group having HbAlc level <7 (6.15%) whereas in females the percentage of mortality was 11.63% in the group having HbAlc ≥7 , higher than the group having HbAlc level <7, 2.5%. Percentage mortality was higher in the patients having HbAlc >7, in both groups’ patients aged below 60 years 14.81% and 17.65% in the group of patients aged above 60 years. Conclusions: Higher HbAlc level significantly affects the outcome of MI patients. The percentage mortality due to MI was higher in male with aged above 60 years and having HbAlc level >7.